Shakespeare's Canon - Charles R.W.D. Moseley (Early Modern Culture Online, 2022)
This essay is concerned  with how Shakespeare himself might have thought about a canon. What for him were the books that, to use A. S. Byatt’s phrase, “every writer had to know in order to know who they are”? One part of that question is easy: the books that every grammar school boy had beaten into him: Livy, Virgil, Ovid, Horace and so on. But how does a writer of his time, and, for that matter, of his calibre, negotiate their legacy?